Implementasi dan Fungsi Sistem Informasi Manajemen Pendidikan Islam bagi Guru - Marfiyah Marfiyah; Uswatun Khasanah; Ali Muhdi (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to conduct an in-depth analysis of the concepts, functions, and implementation of the Islamic Education Management Information System (SIMPI) regarding its role in enhancing the effectiveness of educational management in the digital era. Amid the rapid development of information technology, management information systems have become vital instruments that assist educational institutions in managing data, accelerating information flow, and supporting efficient and measurable decision-making. This study employed a descriptive qualitative method using a library research approach through critical analysis of literature on Islamic education management, information technology, and teacher professionalism. The findings indicate that, from an Islamic perspective, a management information system does not merely function as a data-processing tool, but must also be grounded in spiritual values such as honesty, trustworthiness, responsibility, and justice. For teachers, SIMPI provides significant support in managing student data, preparing instructional documents, evaluating learning outcomes, documenting academic administration, and improving communication among teachers, students, parents, and institutions. Optimal implementation of SIMPI has been shown to support the improvement of teacher professionalism, work efficiency, quality of decision-making, and the overall quality of learning. Therefore, the development of SIMPI in Islamic educational institutions needs to be accompanied by strengthening teachers' digital competence, infrastructure readiness, and the internalization of Islamic ethical values so that technology truly becomes a means of educational benefit.